ANALYSIS OF JOB HAPPINESS, ENERGY EXPENSE AND SWITCH PRODUCTION THAT AFFECT HOME INDUSTRY DEVELOPMENT - Ahmad, Yavi Nabila; Massie, James D. D. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) is the core of the economy in Indonesia. According to the Badan Pusat Statistik (BPS), small and medium businesses are identical to small industries and home industries. The development of a home industry business is a form of business in order to develop even better and to reach a point or peak towards success. This research aims to analyze factors that can affect the home industry development. This study used a quantitative method. A questionnaire is used to collect the data. This research derived and examined the model through the ordinal regression model in a sample of 100 respondents who has running Small Medium business in Minahasa and Manado. The finding of this research shows that job happiness, energy expense, and switching production type influence business development significantly. From the result, it is recommended for the home industry business must be able to prepare themselves and have a strategy in order to produce good quality product. The development of home industry itself is very determined by the owner of the business in managing his business.Keywords: job happiness, energy expense, switching production, home industry development